Gestational diabetes and thyroid disorders in pregnant women in a specialized maternal-child diagnostic center (2022)
Introduction: gestational diabetes mellitus (GDM) commonly appears between the second and third trimesters of pregnancy as a result of hormonal changes that induce a transitory state of insulin resistance (IR) in the mother, allowing a greater supply of glucose to the fetus. After GDM, thyroid disease is the most common endocrine disorder in obstetrics, with an incidence of 5-10%. Some studies speak of the existence of a relationship between diabetes and thyroid disorders (TA) but the results remain controversial, limiting the analysis of the effects that both diseases could have on the development of pregnancy. Therefore, the identification of patients at risk, prevention and timely treatment, constitute one of the priority issues in public health. Objective: in this study, the prevalence of GDM and AT in pregnant women attended in a specialized center for maternal and child diagnosis was analyzed. Materials and methods: retrospective research, based on the exploration of medical records in the period from 2016 to 2020, with a probabilistic sample of 388 pregnant women (n=388). For the diagnosis of GDM, the results of the O'sullivan test, oral glucose tolerance test (OGTT) and fasting blood glucose were taken into account. Thyroid alteration was identified from TSH values, but only 120 pregnant women reported results for this test (n=120). Descriptive measures and simple frequency distributions were calculated. To establish the relationship between GDM and AT, the chi-square test was applied with a statistical significance of p=0.05. Results:the prevalence of GDM was 10.6% (n=41) and of AT 17.5% (n=21). 19% of the pregnant women simultaneously presented GDM and AT with a predominance of a tendency to hyperthyroidism. No significant association was found between GDM and AT (p=0.537). Conclusion: This pilot study confirms that GDM and AT are conditions frequently present in pregnant women. Although there could be a risk of developing GDM in patients with AT, studies with a larger sample number are suggested to clarify this relationship.